Application of the matching law to Mixed Martial Arts. Issue 2 (15th October 2019) - Seniuk, Holly A.; Vu, Janie P.; Nosik, Melissa R.
Abstract : In the contemporary behavior‐analytic literature, athletic performance (e.g., choice of shot or movement) across multiple team sports has been found to correspond with predictions of the generalized matching equation. However, the research in this area has focused primarily on team sports. In the current study the Generalized Matching Equation (GME) was applied to Mixed Martial Arts (MMA) performance by examining strike selection as a function of landing significant strikes among fighters from various weight classes in the Ultimate Fighting Championship. The results suggest that the GME is a good descriptor of strike selection in MMA, an individual sport that is dynamic and fast paced where responding results in immediate feedback from an opponent.